2021
DOI: 10.2147/dmso.s339066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abdominal Obesity in Chinese Middle-Aged and Older Adults with a Normal Body Mass Index and Its Association with Type 2 Diabetes Mellitus: A Nationally Representative Cohort Study from 2011 to 2018

Abstract: Background Few studies have focused on the prevalence of abdominal obesity in Chinese middle-aged and older adults with a normal body mass index (BMI). Furthermore, it is still unclear whether abdominal obesity is an independent risk factor for type 2 diabetes mellitus (T2DM). Participants with a normal BMI are usually neglected during assessments of abdominal obesity-associated T2DM risk since the current recommendations for medical interventions are mainly focused on overall body mass index rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Waist circumference (WC) is a simple, inexpensive, non-invasive anthropometric parameter that directly reflects abdominal obesity. 20–22 Most importantly, some studies have found that TyG-related markers that incorporate obesity indices, such as TyG-WC, are more effective as surrogate markers to reflect the degree of IR than TyG. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…Waist circumference (WC) is a simple, inexpensive, non-invasive anthropometric parameter that directly reflects abdominal obesity. 20–22 Most importantly, some studies have found that TyG-related markers that incorporate obesity indices, such as TyG-WC, are more effective as surrogate markers to reflect the degree of IR than TyG. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…A recent cohort study has shown that abdominal obesity has a positive association with the risk of T2DM in Chinese middle-aged and older adults with normal-BMI. 28 In conclusion, the abdominal ObAIs should be more powerful and sensitive predictors for T2DM compared with BMI. In our study, the ObAI for predicting T2DM was different between men and women.…”
Section: Discussionmentioning
confidence: 89%
“…T2DM is a substantial public health and economic problem worldwide and is common in the general population [ 32 34 ]. Thus, it is crucial that individuals at high risk for T2DM are identified, which may contribute to avoiding an unprecedented increase in the incidence of the disease [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%